Pavlović’s Reading of Folk and Old Serbian Poetry - Despić, Đorđe M. (Poznańskie Studia Slawistyczne, 2021)
Using the analytical method, the paper points to the extents and implications of Pavlović’s research of Serbian verbal folk and medieval literature. Along with this, the paper tries to present this segment of his essayistic work in the context of the wider Pavlović’s essayistic and poetic opus as well, emphasizing their prolific and versatile corresponding. His essays are in a function of thoughtful and evaluating reflections of our oldest literature strata, which eventually shapes up the image about literature and historical span of Serbian poetry and the experience of a unique spiritual continuity. Pavlović’s Essays on Folk and Old Serbian Poetry (orig. Ogledi o narodnoj i staroj srpskoj poeziji) represent an example of how broadness of interests, an impressive intelect, erudite competency, an open and explorative spirit, but also inevitable artistic sensibility and frequent poetic expression become a trigger for new readings and interpretations surely valuable for new generations of readers and researchers.